Removal of total suspended solids and turbidity within experimental vegetated channel: optimization through response surface methodology - Yahyapour, Soheil; Golshan, Abolfazl; Ghazali, Abdul Halim (Elsevier B.V., 2014)
Vegetation plays an important role in transport and settling of suspended sediment in natural waterways. In this study, effectiveness of emergent vegetation in an open channel for the removal of Total Suspended Solids (TSS) and turbidity is empirically investigated. To this end, response surface methodology (RSM) was applied to optimize three variables of vegetated channel including flow velocity at the entrance, density of vegetation, and the length of vegetation zone. Analysis of Variance (ANOVA) was employed to verify the precision of the mathematical models and their relative parameters. Optimum values generated by RSM were compared with experimental results of percentage TSS and turbidity removal and good agreement was observed.